2020
DOI: 10.3390/cancers12102978
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Systems Modelling and Molecular Imaging to Predict the Efficacy of BCL-2 Inhibition in Colorectal Cancer Patient-Derived Xenograft Models

Abstract: Resistance to chemotherapy often results from dysfunctional apoptosis, however multiple proteins with overlapping functions regulate this pathway. We sought to determine whether an extensively validated, deterministic apoptosis systems model, ‘DR_MOMP’, could be used as a stratification tool for the apoptosis sensitiser and BCL-2 antagonist, ABT-199 in patient-derived xenograft (PDX) models of colorectal cancer (CRC). Through quantitative profiling of BCL-2 family proteins, we identified two PDX models which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(87 reference statements)
2
5
0
Order By: Relevance
“…We next showed that modelling the interactions of the BCL-2 protein family upstream of MOMP could also accurately predict sensitivity of medulloblastoma cells to cisplatin-induced apoptosis, with similar results previously observed in colorectal and breast cancer [ 27 , 48 ]. Anti-apoptotic BCL-2 proteins are commonly highly expressed in cancer and are readily targetable by a suite of BH3 mimetics [ 49 ].…”
Section: Discussionsupporting
confidence: 77%
“…We next showed that modelling the interactions of the BCL-2 protein family upstream of MOMP could also accurately predict sensitivity of medulloblastoma cells to cisplatin-induced apoptosis, with similar results previously observed in colorectal and breast cancer [ 27 , 48 ]. Anti-apoptotic BCL-2 proteins are commonly highly expressed in cancer and are readily targetable by a suite of BH3 mimetics [ 49 ].…”
Section: Discussionsupporting
confidence: 77%
“…APOPTO-CELL has also been extensively validated in-house using single cell imaging and population-based approaches in cervical, colorectal and glioblastoma cells (Murphy et al, 2013;Salvucci et al, 2019a;Salvucci et al, 2017;Schmid et al, 2012). Both models have also been shown to predict responses to apoptosis sensitizers in preclinical settings (Lucantoni et al, 2018;O'Farrell et al, 2020). Our study supports the previously developed concept that tumor cells are indeed 'primed' to undergo mitochondrial apoptosis (Llambi et al, 2011;Ni Chonghaile et al, 2011).…”
Section: Priming Of Cancer Cells and The Degree Of Inter-individual Hsupporting
confidence: 79%
“… 120 , 122 The implementing systems and molecular images were established to predict the efficacy of BCL‐2 inhibition in CRC based on a PDX cohort. 123 PP2AC expression accurately indicates therapeutic response to p38 inhibitor in CRC PDX. 124 APC and TP53 mutation as convenient biomarkers predicts the sensitivity to EGFR‐targeted therapies.…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%
“…The expression of EGFR ligands is associated with the sensitivity of CRC to cetuximab, and the gene copy number of some oncogenes ( BRAF , EGFR , and KRAS ) is correlated positively with cetuximab and erlotinib sensitivity 120,122 . The implementing systems and molecular images were established to predict the efficacy of BCL‐2 inhibition in CRC based on a PDX cohort 123 . PP2AC expression accurately indicates therapeutic response to p38 inhibitor in CRC PDX 124 .…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%